Desintegración familiar y su influencia en la conducta emocional de una niña de 11 años - Vera Cardenas, Andrea Tatiana (2020)
In the following study it is to treat family disintegration and its influence on emotional behavior which is related to the general objective whether or not there is an influence towards the child's emotional behavior, with their respective lines and sub-line of research. To carry out this research, different psychological batteries are applied to obtain better results such as the Family test, to see the family relationship, the patient's family attachment. Bender's test to observe, assess the emotional components of the child, also applied the depression Inventory test, including clinical history, interview, techniques that improve information collection. After the qualification of the different tests applied, some affected areas were detected, such as the affective area, area of thought and socio-school area. Therefore, several techniques are applied to improve the patient's quality of life, such as roll playing, the cost-benefit form, techniques that help the patient reduce or eliminate the thoughts and beliefs that are the triggering factor of his problem. In addition, it is identified if family breakdown influences the emotional behavior of the patient.